2007
DOI: 10.1111/j.1365-313x.2007.03219.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and biochemical evidence links the callose synthase in Nicotiana alata pollen tubes to the product of the NaGSL1 gene

Abstract: SummaryThe NaGSL1 gene has been proposed to encode the callose synthase (CalS) enzyme from Nicotiana alata pollen tubes based on its similarity to fungal 1,3-b-glucan synthases and its high expression in pollen and pollen tubes. We have used a biochemical approach to link the NaGSL1 protein with CalS enzymic activity. The CalS enzyme from N. alata pollen tubes was enriched over 100-fold using membrane fractionation and product entrapment. A 220 kDa polypeptide, the correct molecular weight to be NaGSL1, was sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…The GSL genes encode (1,3)-␤-D-glucan synthases (callose synthases) (7,8), and the CESA genes encode cellulose synthases (9). The CSLs are believed to encode enzymes that synthesize the backbone of various non-cellulosic ␤-linked polysaccharides of the wall (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…The GSL genes encode (1,3)-␤-D-glucan synthases (callose synthases) (7,8), and the CESA genes encode cellulose synthases (9). The CSLs are believed to encode enzymes that synthesize the backbone of various non-cellulosic ␤-linked polysaccharides of the wall (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…It was hypothesized that the same enzyme may be involved in the biosynthesis of callose and cellulose and that the biosynthesis of either polysaccharide may be controlled by phosphorylation (Delmer, 1999). However, experimental data showed that the cellulose and callose synthase catalytic subunits are encoded by different genes (Pear et al, 1996;Arioli et al, 1998;Cui et al, 2001;Doblin et al, 2001;Hong et al, 2001a;Li et al, 2003;Brownfield et al, 2007). Indeed, these proteins show no significant sequence similarity and are grouped in different glycosyltransferase families in the CAZY database (http:// www.cazy.org), family 2 for cellulose synthase and family 48 for callose synthase (Cantarel et al, 2009).…”
mentioning
confidence: 99%
“…Callose is also the main component of callose plugs, which form regularly in the mature region and allow cytoplasm to concentrate in the tube apex (Cresti and VanWent, 1976). Callose is produced by the enzyme callose synthase (Brownfield et al, 2007), which is localized in the plasma membrane (Ferguson et al, 1998). Cellulose occurs in lower quantities than callose (Schlupmann et al, 1994) and is generally localized in the inner layer of the cell wall (Ferguson et al, 1998).…”
mentioning
confidence: 99%